Essential oil composition, insecticidal and antibacterial activities of Salvia tomentosa Miller - Ulukanli, Zeynep; Karaborklu, Salih; Cenet, Menderes; Sagdic, Osman; Ozturk, Ismet; Balcilar, Mehmet (SPRINGER BIRKHAUSER, 2013)
The effectiveness of the essential oil of Salvia tomentosa Miller was assessed on two important pest insects and seven pathogenic bacteria. The essential oil of aerial parts of this plant was hydro-distillated using a clevenger-type apparatus (yield 0.31 % v/w) and constituents were determined using GC-MS analysis. beta-pinene (37.28 %) and alpha-pinene (5.73 %) were the predominant chemical constituents, followed by trans-pinocarveol (3.05 %), myrtenol (2.81 %), caryphyllene oxide (2.68 %), d-camphor (2.08 %). The complete mortality was determined at above doses of 50 mu l L-1 air on Acanthoscelides obtectus (Say) adults. However, the essential oil in concern caused 83.34 and 100 % mortality at higher doses (150 and 200 mu l L-1 air) against Tribolium castaneum (Herbst) adults. The essential oil also revealed significant bacteriostatic and bactericidal activities against Staphylococcus aureus, Bacillus subtilis, Bacillus cereus, Micrococcus luteus, Escherichia coli, Enterobacter aerogenes and Yersinia enterocolitica. The essential oil of S. tomentosa in concern can be used as a potential insecticide and bactericidal agents in food applications and agricultural commodities and/or other fields.
Keywords: Balsamic sage; Antibacterial activity; Insecticidal activity; Essential oil; Lamiaceae; PLANT ESSENTIAL OILS; CHEMICAL-COMPOSITION; FUMIGANT TOXICITY; ANTIMICROBIAL PROPERTIES; METHANOL EXTRACTS; AERIAL PARTS; ANTIOXIDANT; L.; THYMUS; Pharmacology & Pharmacy